Membudayakan Penggunaan Bahasa Arab Pada Siswa di Lingkungan Sekolah SD IT Al-Izzah Sibuhuan Kecamatan Barumun Kabupaten Padang Lawas - Nurhalimah Harahap; Robiatul Adawiyah Pohan; Halimah Nasution; Anita Rahman Hrp (CV Putra Publisher, 2023)
This community service activity is realized with a program to use the Arabic language to add insight to students. The activity of using Arabic was carried out in the IT AL-IZZAH Sibuhuan SD school environment, Barumun District, Padang Lawas Regency. The purpose of this activity is to guide students to have good and correct Arabic language skills. The main problem faced by children when they hear Arabic is the paradigm that Arabic is very difficult to understand and learn. This resulted in a decrease in students' interest in learning Arabic so that it could not be applied in everyday life. This service activity is in the form of a language tutoring program that goes according to plan and is carried out for all students. These results were obtained from the direct approach method by introducing Arabic after each sunnah dhuha prayer and zduhur prayer. The material presented is in the form of introductions or at-ta'aruf, then vocabulary or al-mufrodat, daily conversation and introduction to dhomir. The expected end result of this language guidance is that students are able to apply the use of Arabic in everyday life and overcome the difficulties that children face when learning Arabic. Children can learn calmly, comfortably, and are able to understand the material presented